Characterisation and prognosis of the capillary rise of fluids in textile structures, exemplified by wicking of sunflower oil into cotton nonwovens. (2017) - Maschler, Tobias; Finckh, Hermann; Stegmaier, Thomas; Tilebein, Meike; Gresser, Götz T.
Abstract: Although there are several methods for describing the absorption behaviour of textile structures, there is no such one yet for identifying the material and fluid parameters that are necessary for simulating the dynamics of the capillary rise of fluids in textile structures. This contribution describes a parameter identification method for a general model for wicking in capillary systems composed of a porous material and a liquid. The resulting characterisation enables modelling and optimising wicking of fluids in textile structures – not only from a static point of view, but as well from a dynamic one. With such acquired knowledge, it is possible to optimise e.g. the wicking effect or liquid absorption volume in absorber structures by modifying the product's composition, its construction, and surface finish. The contribution describes the underlying model from a physical-mathematical point of view and shows sample characterisations for vertical and horizontal wicking of sunflower oil in hydro-entangled cotton nonwovens.